South Africa : Report on Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2010)
South Africa has made good progress in developing its system for combating money laundering (ML) and financing of terrorism (FT). The report provides a summary of the Anti- Money Laundering/Combating the Financing of Terrorism (AML/CFT) measures and also contains recommendations on how the AML/CFT system could be strengthened. South Africa has adopted mechanisms to freeze terrorist-related assets and also demonstrated a strong commitment to implementing AML/CFT systems, which have involved close cooperation and coordination between a variety of government departments and agencies. The country has established effective mechanism to combat ML and FT.